2015
DOI: 10.3389/fmicb.2015.00762
|View full text |Cite
|
Sign up to set email alerts
|

Reutericyclin producing Lactobacillus reuteri modulates development of fecal microbiota in weanling pigs

Abstract: Lactobacillus reuteri is used as probiotic culture in food and feed applications; however, strain specific properties of L. reuteri that mediate probiotic activity remain unknown. This study aimed to determine effects of feed fermentation with exopolysaccharide and reutericyclin producing L. reuteri on the transition of the gut microbiome of piglets after weaning. The reutericyclin and reuteran producing L. reuteri TMW1.656 was compared to the reutericyclin negative and levan producing L. reuteri LTH5794 and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…In addition, we have shown that L reuteri cell‐free supernatant was as effective in inhibiting P gingivalis as living bacteria, suggesting that microbial growth reduction was mainly due to the substances produced by the probiotic. Besides reuterin, L reuteri strains produce a series of other antimicrobial substances, including lactic acid, acetic acid, ethanol, and reutericyclin . The literature has also shown the importance of the acidic environment in the interactions between L reuteri and other microorganisms .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have shown that L reuteri cell‐free supernatant was as effective in inhibiting P gingivalis as living bacteria, suggesting that microbial growth reduction was mainly due to the substances produced by the probiotic. Besides reuterin, L reuteri strains produce a series of other antimicrobial substances, including lactic acid, acetic acid, ethanol, and reutericyclin . The literature has also shown the importance of the acidic environment in the interactions between L reuteri and other microorganisms .…”
Section: Discussionmentioning
confidence: 99%
“…; Yang et al . ), adhesion to the mucus layer (Lee and Puong ; Valeriano et al . ), antioxidative capacity (Wang et al .…”
Section: The Role Of Lactobacilli In Swine Husbandrymentioning
confidence: 99%
“…; Yang et al . ). Recently, new omics techniques have provided more accurate and practical tools for screening and discovery of beneficial Lactobacillus strains from the GIT as probiotic candidates for the swine industry.…”
Section: Introductionmentioning
confidence: 97%
“…61,62 In vitro studies have demonstrated strain specific anti-inflammatory effects via suppression of tumor necrosis factor (TNF) in activated human macrophages. 63 In a rat model of NEC, L reuteri strains DSM 17938 and ATCC PTA 4659 decreased the incidence and severity of NEC, decreased mRNA expression of IL-6, TNF-α, TLR4, and NF-κB and protein expression of TLR4, TNF-α and IL-1β and increased numbers of regulatory T cells in the ileum.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%